Management of the Floating Knee: Ipsilateral Fractures of the Femur and Tibia. Issue 2 (15th January 2020) - Vallier, Heather A.; Manzano, Givenchy W.
Abstract : The "floating knee" is defined as fractures of the ipsilateral femur and tibia, which consists of a spectrum of injury, and may be in isolation or part of multiple system trauma for a given patient. A floating knee may compromise limb viability due to severe soft-tissue and vascular injury. Expeditious fracture reduction and patient resuscitation are crucial, while type and timing of provisional and definitive management is guided by the extent of injury to the involved extremity and associated systemic injuries. Numerous surgical techniques are available to treat the floating knee, including external fixation and internal fixation with plates or intramedullary nails. Fracture complexity and severity of soft-tissue injury present challenges, with articular injuries potentially more debilitating in the long term. Complications such as infection, deep vein thrombosis, knee stiffness, nonunion, malunion, and posttraumatic arthrosis after these injuries should be considered.